Thoracoamniotic shunt for fetal hydrothorax: A case report - Huertas Tacchino, Erasmo (2019)
We report a case of massive unilateral hydrothorax diagnosed in an 18-weeks-old fetus with a normal karyotype. The fetus was severely affected by hydrops and bradycardia since week 24. Initially, we performed pleurodesis, but the hydrothorax worsened and evolved into hydrops, so we proceeded to insert a transplacental thoracoamniotic shunt. Improvement was evident one week after the procedure, and the hydrothorax resolved during the remainder of the pregnancy. Following cesarean delivery at 37 weeks, the neonate required prolonged NICU stay. He was discharged after two months and remains stable until the present time.